Double-doped high-stability positive electrode material as well as preparation method and application thereof

Dual-site doping of zinc and copper in sodium-ion battery materials stabilizes the P2 phase structure, improving cycle stability and sodium ion diffusion, addressing structural transformation issues in P2-phase layered transition metal oxides.

CN119208582APending Publication Date: 2024-12-27LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310759987.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

P2-phase layered transition metal oxides in sodium-ion batteries suffer from structural transformation during charge and discharge, leading to poor cycle stability and rate performance due to layer slip under deep desodiumization.

Method used

A dual-site doping method is employed, where zinc ions are doped at sodium sites to form O 2- -Zn 2+ -O 2- prismatic structures, and copper ions partially replace Mn 3+ in the transition metal sites, stabilizing the layered structure and reducing interface diffusion activation energy.

Benefits of technology

The dual-site doping enhances the cycle stability and air stability of the positive electrode material, increasing the diffusion rate of sodium ions and achieving long-term stable cycling at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208582A_ABST
    Figure CN119208582A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a double-doped high-stability positive electrode material and a preparation method and application thereof, the chemical general formula of the high-stability positive electrode material is NaxZnyMn1-zCuzO2, wherein x is more than or equal to 0.4 and less than or equal to 0.7, y is more than or equal to 0.01 and less than or equal to 0.25, and z is more than or equal to 0.05 and less than or equal to 0.3; zinc ions doped in sodium sites in the high-stability positive electrode material form an O2--Zn < 2 + >-O < 2-> prism structure; cu < 2 + > provided by transition metal site doping in the high-stability positive electrode material partially replaces Mn < 3 + >; when the two-site doped high-stability positive electrode material is applied to a sodium ion battery, due to the fact that the material adopts a zinc and copper two-site doping mode, the interface diffusion activation energy of sodium ions is reduced while the structure of the positive electrode material is stabilized, the diffusion rate of the sodium ions in a bulk phase is increased, and the stability of the sodium ion battery is improved. And the long-acting stable circulation of the sodium ion battery under high voltage is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a dual-site doped high-stability positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of lithium-ion batteries in recent years, lithium batteries have begun to be widely used in energy storage systems and electric vehicle markets; this has led to an explosive growth in the demand for lithium batteries, but the storage capacity and rising prices of lithium metal have become key obstacles to the development of lithium batteries; therefore, sodium-ion batteries, which are low-cost and have similar physical and chemical properties to lithium-ion batteries, are considered to be ideal candidates for large-scale electrical energy storage.

[0003] At present, sodium-ion batteries are developing rapidly. P2-phase layered transition metal oxides with high ionic conductivity show great application potential as positive electrode materials for sodium-ion batteries. However, the positive electrode undergoes a structural transformation from P2 phase to O2 phase during the charge and discharge process, resulting in poor cycle stability and rate performance.

[0004] Therefore, how to solve the layer slip that occurs under deep desodiumization state is an urgent problem that needs to be solved for P2 phase layered transition metal oxides as positive electrode materials for sodium ion batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a dual-site doped high-stability positive electrode material and its preparation method and application. The dual-site doped high-stability positive electrode material prepared by the present invention, wherein zinc ions are doped at sodium sites to form O 2- -Zn 2+ -O 2- The prismatic structure can effectively increase the electrostatic attraction between zinc ions and oxygen ions, strengthen the stability of the layered structure, and thus make the material have good cycle stability and air stability; at the same time, an appropriate amount of copper can partially replace the Mn of the manganese-based material. 3+ , inhibiting the Mn 3+ The dissolution in the high voltage region improves the cycle stability of the positive electrode material. The dual-site doped high-stability positive electrode material of the present invention adopts the dual-site doping method of zinc and copper to stabilize the structure of the positive electrode material while reducing the interface diffusion activation energy of sodium ions, increasing the diffusion rate of sodium ions in the bulk phase, and realizing the long-term stable cycle of sodium ion batteries at high voltage.

[0006] To this end, in a first aspect, an embodiment of the present invention provides a dual-site doped high-stability positive electrode material, the chemical formula of the high-stability positive electrode material is Na x Zn y Mn 1-z Cu zO2, where 0.4≤x≤0.7, 0.01≤y≤0.25, 0.05≤z≤0.3;

[0007] The phase structure of the high-stability positive electrode material is a P2 phase;

[0008] The zinc ions doped in the sodium sites of the high-stability cathode material form O 2- -Zn 2+ -O 2- The prismatic structure;

[0009] The transition metal sites in the high stability cathode material are doped with Cu 2+ Partially replace Mn 3+ .

[0010] Preferably, the particle size Dv50 of the high-stability positive electrode material is between 1 μm and 50 μm.

[0011] In a second aspect, an embodiment of the present invention provides a method for preparing a dual-site doped high-stability positive electrode material according to the first aspect, the preparation method comprising:

[0012] Step S1, stirring and dissolving the required raw materials to obtain a mixed solution, specifically: weighing a soluble sodium source material, a zinc source material, a manganese source material, a copper source material and deionized water according to a stoichiometric ratio, adding them into a disperser, stirring and dissolving them uniformly, to obtain a mixed solution;

[0013] Step S2, preparing the precursor gel by hydrothermal reaction, specifically: putting the mixed solution obtained above and the complexing agent into a hydrothermal reaction kettle, controlling the water bath temperature and adding ammonia water to adjust the pH value, stirring and reacting for a certain period of time to obtain the precursor gel;

[0014] Step S3, drying and sintering the precursor gel to prepare a high-stability positive electrode material: drying the precursor gel obtained above in an oven, grinding it into powder, sintering it at high temperature, and cooling it to room temperature to obtain a dual-site doped high-stability positive electrode material.

[0015] Preferably, the sodium source material includes: one or more of sodium hydroxide, sodium chloride, sodium fluoride, sodium nitrate, sodium carbonate, and sodium bicarbonate;

[0016] The zinc source material includes: one or more of zinc chloride, zinc sulfate, zinc nitrate, zinc acetate, and zinc nitrate hexahydrate;

[0017] The manganese source material includes: one or more of manganese nitrate, manganese sulfate, manganese acetate, manganese chloride, and acid manganese phosphate;

[0018] The copper source material includes: one or more of copper chloride, copper sulfate, and copper nitrate.

[0019] Preferably, the solid content of the mixed solution is between 10% and 50%;

[0020] The mass of the complexing agent is 2%-15% of the mass of the mixed solution.

[0021] Preferably, the pH value of the ammonia water is adjusted to be in the range of 5.5-6.3.

[0022] Preferably, the water bath temperature is between 30°C and 80°C; and the stirring reaction time is 1 hour to 12 hours.

[0023] Preferably, the drying temperature of the oven is 60° C.-120° C., and the drying time is 3 hours-15 hours.

[0024] Preferably, the high temperature sintering is specifically carried out by heating the temperature to 750°C-1000°C at a heating rate of 1°C / min-10°C / min, and the heat preservation time is 8 hours-24 hours.

[0025] In a third aspect, an embodiment of the present invention provides a sodium ion battery, comprising the double-site doped high-stability positive electrode material of the first aspect.

[0026] The high stability positive electrode material doped at a dual site provided by the embodiment of the present invention adopts a doping method of zinc and copper dual sites, wherein zinc ions are doped at the sodium site to form O 2- -Zn 2+ -O 2- The prismatic structure can effectively increase the electrostatic attraction between zinc ions and oxygen ions, strengthen the stability of the layered structure, and thus make the material have good cycle stability and air stability; the appropriate amount of doped copper ions can partially replace the Mn of the manganese-based material. 3+ , inhibiting the Mn 3+ Dissolution in the high voltage region improves the cycling stability of the material.

[0027] The dual-site doped high-stability positive electrode material of the present invention is used in a sodium ion battery. Due to the adoption of the above-mentioned zinc and copper dual-site doping method, the interface diffusion activation energy of sodium ions is reduced while stabilizing the structure of the positive electrode material, the diffusion rate of sodium ions in the bulk phase is increased, and a long-term stable cycle of the sodium ion battery at a high voltage is achieved.

[0028] The method for preparing a dual-site doped high-stability positive electrode material provided by the embodiment of the present invention has simple operation, low cost, and is applicable to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1A flow chart of a method for preparing a dual-site doped high-stability positive electrode material provided in an embodiment of the present invention;

[0030] Figure 2 A comparison diagram of the cycle performance curves of button-type batteries assembled in Example 1 of the present invention and Comparative Example 1;

[0031] Figure 3 It is a comparison chart of the rate cycle test of button-type batteries assembled in Example 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0032] The present invention is described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0033] The embodiment of the present invention provides a dual-site doped high-stability positive electrode material, the phase structure is P2 phase, and its chemical formula is Na x Zn y Mn 1-z Cu z O2, wherein 0.4≤x≤0.7, 0.01≤y≤0.25, 0.05≤z≤0.3; the particle size Dv50 of the high-stability positive electrode material is between 1μm-50μm.

[0034] The high stability positive electrode material of the present invention adopts zinc ions (Zn 2+ ) and copper ions (Cu 2+ )Dual-site doping method.

[0035] Among them, the zinc ions doped in the sodium site form O 2- -Zn 2+ -O 2- The prismatic structure of Zn 2+ Doping replaces sodium vacancies, making Zn 2+ With O 2- Interacting with each other can effectively increase Zn 2+ With O 2- The electrostatic attraction between them inhibits the transformation of the material structure from P2 phase to O2 phase during the charge and discharge process, strengthens the stability of the layered structure, and avoids the collapse of the material structure, thereby giving the material good cycle stability and air stability.

[0036] The Cu provided by transition metal site doping 2+ Partially replace Mn 3+ , inhibiting the Mn 3+ Dissolution in the high voltage region improves the cycling stability of the material.

[0037] The present invention provides a method for preparing the above-mentioned dual-site doped high-stability positive electrode material, such as Figure 1 As shown, the preparation method comprises the following steps:

[0038] Step S1, stirring and dissolving the required raw materials to obtain a mixed solution, specifically: weighing a soluble sodium source material, a zinc source material, a manganese source material, a copper source material and deionized water according to a stoichiometric ratio, adding them into a disperser, stirring and dissolving them uniformly, to obtain a mixed solution;

[0039] Wherein, the sodium source material includes: one or more of sodium hydroxide, sodium chloride, sodium fluoride, sodium nitrate, sodium carbonate, and sodium bicarbonate;

[0040] The zinc source material includes: one or more of zinc chloride, zinc sulfate, zinc nitrate, zinc acetate, and zinc nitrate hexahydrate;

[0041] The manganese source material includes: one or more of manganese nitrate, manganese sulfate, manganese acetate, manganese chloride, and acid manganese phosphate;

[0042] The copper source material includes: one or more of copper chloride, copper sulfate, and copper nitrate;

[0043] The solid content in the mixed solution is between 10% and 50%.

[0044] Step S2, preparing the precursor gel by hydrothermal reaction, specifically: putting the mixed solution obtained above and the complexing agent into a hydrothermal reaction kettle, controlling the water bath temperature and adding ammonia water to adjust the pH value, stirring and reacting for a certain period of time to obtain the precursor gel;

[0045] Wherein, the mass of the complexing agent is 2%-15% of the mass of the mixed solution;

[0046] Ammonia water adjusts the pH value to between 5.5-6.3;

[0047] The water bath temperature is between 30°C and 80°C; the stirring reaction time is 1 hour to 12 hours.

[0048] Step S3, drying and sintering the precursor gel to prepare a high-stability positive electrode material: drying the precursor gel obtained above in an oven, grinding it into powder, sintering it at high temperature, and cooling it to room temperature to obtain a dual-site doped high-stability positive electrode material;

[0049] The drying temperature of the oven is 60°C-120°C, and the drying time is 3 hours-15 hours;

[0050] The high temperature sintering is specifically carried out by heating the temperature to 750°C-1000°C at a heating rate of 1°C / min-10°C / min, and the heat preservation time is 8 hours-24 hours.

[0051] The dual-site doped high-stability positive electrode material prepared by the above preparation method can be used together with commonly used binders and conductive agents to prepare positive electrode sheets through conventional methods.

[0052] A positive electrode sheet containing a double-site doped high-stability positive electrode material can be assembled with a separator, an electrolyte or a solid electrolyte, and a negative electrode sheet to form a sodium ion battery.

[0053] Among them, the diaphragm includes but is not limited to any one of a double-sided alumina diaphragm and a diaphragm containing a sodium ion solid electrolyte; the base film of the diaphragm includes: any one of a polyolefin film, a non-woven fabric diaphragm, a fiber diaphragm, and a polyaramid diaphragm.

[0054] The negative electrode plate includes any one of a sodium sheet or a negative electrode current collector containing a negative electrode active material; specifically, the negative electrode current collector includes but is not limited to aluminum foil, copper foil or titanium foil, and the active material layer on the surface of the negative electrode current collector also contains commonly used conductive agents and binders; the negative electrode active material includes but is not limited to any one of a carbon material, a tin-based negative electrode material, a silicon-based negative electrode material, a silicon-carbon composite material, a nano-oxide material, and a titanate negative electrode material; the carbon material includes any one of graphite, hard carbon, carbon fiber, petroleum coke, and mesophase carbon microbeads.

[0055] The electrolyte includes a solute and a solvent; wherein the solute is a conductive salt, including any one of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium hexafluoroarsenate (NaAsF6), and sodium trifluoroacetate (CF3COONa); the solvent includes ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropylene carbonate (DPC), and ethylene carbonate (EC). ester (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), γ-butyrolactone (BL), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), propyl propionate (PP), ethyl butyrate (EB), 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), triethylene glycol dimethyl ether (TRGDME), tetraethylene glycol dimethyl ether (TEGDME), ethyl methanesulfonate (EMS) or dimethyl sulfoxide (DMSO).

[0056] In the sodium ion battery containing a dual-site doped high-stability positive electrode material provided by the embodiment of the present invention, during the charge and discharge cycle, the high-stability positive electrode material adopts a dual-site doping method of zinc ions and copper ions; the zinc ions doped in the sodium site form O 2- -Zn 2+ -O 2-The prismatic structure can inhibit the material structure from transforming from the P2 phase to the O2 phase during the charge and discharge process, strengthen the stability of the layered structure, and avoid the collapse of the material structure; and the Cu provided by the transition metal site doping 2+ Partially replace Mn 3+ , reducing the amount of Mn that undergoes disproportionation during the charge and discharge process 3+ , thereby reducing the Mn 3+ To Mn 2+ The side reactions of the transformation reduce the Mn 2+ Dissolution in the electrolyte in the high voltage area reduces the risk of material structure collapse and improves the material's cycle stability.

[0057] Therefore, the dual-site doped high-stability positive electrode material of the present invention is applied to sodium ion batteries, which stabilizes the structure of the positive electrode material while reducing the interfacial diffusion activation energy of sodium ions and increasing the diffusion rate of sodium ions in the bulk phase, thereby achieving long-term stable circulation of sodium ion batteries at high voltage.

[0058] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the dual-site doped high-stability positive electrode material of the present invention are respectively described below with multiple specific examples.

[0059] Example 1

[0060] This embodiment provides a preparation process and performance test of a dual-site doped high-stability positive electrode material, and the specific process is as follows:

[0061] (1) Stirring and dissolving the required raw materials to obtain a mixed solution, specifically: weighing soluble sodium carbonate, zinc chloride, manganese acetate, copper chloride and deionized water according to the required stoichiometric ratio, adding them into a disperser, stirring and dissolving them uniformly, and the total mass of the obtained mixed solution is 3 kg, wherein the mass fraction of the solid content is 25%.

[0062] (2) The precursor gel is prepared by a hydrothermal reaction, specifically: the mixed solution obtained above and 5% by weight of the complexing agent citric acid are added into a hydrothermal reactor, the water bath temperature is controlled at 60°C and ammonia water is added to adjust the pH value to 5.8, and the precursor gel is obtained after stirring for 4 hours.

[0063] (3) Drying and sintering the precursor gel to prepare a high-stability positive electrode material: The precursor gel obtained above was dried in an oven at 80°C for 5 hours, ground into powder, and then sintered at high temperature. The temperature was raised to 800°C at a heating rate of 5°C / min, kept at this temperature for 15 hours, and cooled to room temperature to obtain a high-stability double-site doped positive electrode material with a particle size Dv50 of 8.3 μm. The chemical formula is: Na 0.67 Zn 0.05 Mn 0.75 Cu0.25 O2.

[0064] The positive electrode sheet was prepared using the double-site doped high-stability positive electrode material prepared in Example 1 of the present invention and assembled into a button cell for testing. The preparation process and the testing process are as follows:

[0065] Preparation of positive electrode sheet: The dual-site doped high-stability positive electrode material prepared in this embodiment is homogenized with polyvinylidene fluoride (PVDF) and conductive carbon black (SP) in a mass ratio of 93:5:2 to form a slurry, which is then coated on aluminum foil to prepare a positive electrode sheet.

[0066] Assembly of button cells: A positive electrode sheet coated with the dual-site doped high-stability positive electrode material prepared in this embodiment, a polypropylene PP separator, a hard carbon negative electrode sheet and a 1M NaPF6 electrolyte are assembled into a button cell using conventional methods.

[0067] The test method for button batteries is as follows: charge at a constant current rate of 0.1C to a voltage of 4.0V, then let it stand for 5 minutes, then discharge at a constant current rate of 0.1C to a voltage of 2.0V, and then let it stand for 5 minutes as a cycle charge and discharge process, and perform 100 cycles of charge and discharge tests according to the above method.

[0068] The cycle curve of the button battery in this embodiment is as follows: Figure 2 shown.

[0069] Example 2

[0070] This embodiment provides a preparation process and performance test of a dual-site doped high-stability positive electrode material, and the specific process is as follows:

[0071] (1) Stirring and dissolving the required raw materials to obtain a mixed solution, specifically: weighing soluble sodium hydroxide, zinc nitrate hexahydrate, manganese nitrate, copper nitrate and deionized water according to the required stoichiometric ratio, adding them into a disperser, stirring and dissolving them uniformly, and the total mass of the obtained mixed solution is 4 kg, wherein the mass fraction of the solid content is 20%.

[0072] (2) The precursor gel is prepared by a hydrothermal reaction, specifically: the mixed solution obtained above and 4% by weight of the complexing agent oxalic acid are added into a hydrothermal reactor, the water bath temperature is controlled at 80°C and ammonia water is added to adjust the pH value to 6.0, and the precursor gel is obtained after stirring for 3 hours.

[0073] (3) Drying and sintering the precursor gel to prepare a high-stability positive electrode material: The precursor gel obtained above was dried in an oven at 60°C for 8 hours, ground into powder, and then sintered at high temperature. The temperature was raised to 950°C at a heating rate of 5°C / min, kept at this temperature for 12 hours, and cooled to room temperature to obtain a high-stability double-site doped positive electrode material with a particle size Dv50 of 7.9 μm. The chemical formula is: Na 0.44 Zn 0.1 Mn 0.9 Cu 0.1 O2.

[0074] The positive electrode sheet was prepared using the double-site doped high-stability positive electrode material prepared in Example 2 of the present invention and assembled into button cells for testing. The preparation process of the battery was the same as the method in Example 1.

[0075] The rate performance of the button cell of this embodiment was tested, and the specific method was as follows: first, the battery was charged to 4.0V at a rate of 0.1C, and then the current was reduced to 0.05C at a constant voltage of 4.0V, and then the battery was discharged to 2.75V at a rate of 0.1C, and the cycle was repeated for 5 cycles; then the battery was charged to 4.0V at a rate of 0.2C, and then the current was reduced to 0.05C at a constant voltage of 4.0V, and then the battery was discharged to 2.75V at a rate of 0.2C, and the cycle was repeated for 5 cycles; then the battery was charged to 4.0V at a rate of 0.5C, and then the current was reduced to 0.05C at a constant voltage of 4.0V, and then the battery was discharged to 2.75V at a rate of 0.5C, and the cycle was repeated for 5 cycles; then the battery was charged to 4.0V at a rate of 1C, and then the current was reduced to 0.05C at a constant voltage of 4.0V, and then the battery was discharged to 2.75V at a rate of 1C, and then the battery was charged to 4.0V at a constant voltage of 4.0V, and then the battery was discharged to 2.75V at a rate of 1C, and then the battery was discharged to 2.75V at a rate of 1C, and then the battery was discharged to 2.75V at a rate of 1C, and then the battery was discharged to 4.0V at a constant voltage of 4.0V, and then the battery was discharged to 2.75V at a rate of 1C, and then the battery was discharged to 2.75V at a rate of 1C, and then the battery was discharged to 2.75V at a rate of 1C.

[0076] Battery rate cycle test chart, such as Figure 3 shown.

[0077] Example 3

[0078] This embodiment provides a preparation process and performance test of a dual-site doped high-stability positive electrode material, and the specific process is as follows:

[0079] (1) Stirring and dissolving the required raw materials to obtain a mixed solution, specifically: weighing soluble sodium carbonate, zinc nitrate hexahydrate, manganese nitrate, copper chloride and deionized water according to the required stoichiometric ratio, adding them into a disperser, stirring and dissolving them uniformly, and the total mass of the obtained mixed solution is 3.5 kg, wherein the mass fraction of the solid content is 23%.

[0080] (2) The precursor gel is prepared by a hydrothermal reaction, specifically: the mixed solution obtained above and 4% by weight of the complexing agent oxalic acid are added into a hydrothermal reactor, the water bath temperature is controlled at 50°C, and ammonia water is added to adjust the pH value to 5.6. After stirring and reacting for 5 hours, the precursor gel is obtained.

[0081] (3) Drying and sintering the precursor gel to prepare a high-stability positive electrode material: The precursor gel obtained above was dried in an oven at 100°C for 3 hours, ground into powder, and then sintered at high temperature. The temperature was raised to 900°C at a heating rate of 5°C / min, kept at this temperature for 20 hours, and cooled to room temperature to obtain a high-stability double-site doped positive electrode material with a particle size Dv50 of 9.5 μm. The chemical formula is: Na 0.6 Zn 0.1 Mn 0.83 Cu 0.17 O2.

[0082] Example 4

[0083] This embodiment provides a preparation process and performance test of a dual-site doped high-stability positive electrode material, and the specific process is as follows:

[0084] (1) Stirring and dissolving the required raw materials to obtain a mixed solution, specifically: weighing soluble sodium chloride, zinc acetate, manganese acetate, copper chloride and deionized water according to the required stoichiometric ratio, adding them into a disperser, stirring and dissolving them uniformly, and the total mass of the obtained mixed solution is 4.0 kg, wherein the mass fraction of the solid content is 25%.

[0085] (2) The precursor gel is prepared by a hydrothermal reaction, specifically: the mixed solution obtained above and 4% by weight of the complexing agent oxalic acid are added into a hydrothermal reactor, the water bath temperature is controlled to 80°C and ammonia water is added to adjust the pH value to 6.0, and the precursor gel is obtained after stirring for 5 hours.

[0086] (3) Drying and sintering the precursor gel to prepare a high-stability positive electrode material: The precursor gel obtained above was dried in an oven at 100°C for 3 hours, ground into powder, and then sintered at high temperature. The temperature was raised to 950°C at a heating rate of 5°C / min, kept at this temperature for 15 hours, and cooled to room temperature to obtain a high-stability double-site doped positive electrode material with a particle size Dv50 of 11.2 μm. The chemical formula is: Na 0.66 Zn 0.08 Mn 0.72 Cu 0.28 O2.

[0087] In order to better illustrate the effects of the embodiments of the present invention, comparative example 1 is compared with embodiment 1 and embodiment 2.

[0088] Comparative Example 1

[0089] The positive electrode sheet coated with undoped sodium manganate positive electrode material, the polypropylene PP separator, the hard carbon negative electrode sheet and the 1M NaPF6 electrolyte were assembled into a button cell by conventional methods.

[0090] The cycle performance and rate performance were tested according to the test methods of Example 1 and Example 2, and the cycle curves were obtained as shown in Figure 2 As shown in the figure, the rate cycle test diagram is as follows Figure 3 As shown in the figure, it can be seen that the button cells of Example 1 and Example 2 contain high-stability positive electrode materials doped with zinc ions and copper ions, the cycle performance of Example 1 and the rate performance of Example 2 are significantly higher than those of the button cell of Comparative Example 1 that is not doped, indicating that the stability of the structure of the high-stability positive electrode material containing dual-site doping of the present invention is significantly higher than the stability of the undoped positive electrode material structure, and therefore the dual-site doped high-stability positive electrode material of the present invention has better cycle performance and rate performance.

[0091] The high stability positive electrode material doped at a dual site provided by the embodiment of the present invention adopts a doping method of zinc and copper dual sites, wherein zinc ions are doped at the sodium site to form O 2- -Zn 2+ -O 2- The prismatic structure can effectively increase the electrostatic attraction between zinc ions and oxygen ions, strengthen the stability of the layered structure, and thus make the material have good cycle stability and air stability; the appropriate amount of doped copper ions can partially replace the Mn of the manganese-based material. 3+ , inhibiting the Mn 3+ Dissolution in the high voltage region improves the cycle stability of the positive electrode material.

[0092] The dual-site doped high-stability positive electrode material of the present invention is used in a sodium ion battery. Due to the adoption of the above-mentioned zinc and copper dual-site doping method, the interface diffusion activation energy of sodium ions is reduced while stabilizing the structure of the positive electrode material, the diffusion rate of sodium ions in the bulk phase is increased, and a long-term stable cycle of the sodium ion battery at a high voltage is achieved.

[0093] The method for preparing a dual-site doped high-stability positive electrode material provided by the embodiment of the present invention has simple operation, low cost, and is applicable to large-scale production.

[0094] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A dual-site doped high-stability positive electrode material, characterized in that: The chemical formula of the high stability positive electrode material is Na x Zn y Mn 1-z Cu z O2, where 0.4≤x≤0.7, 0.01≤y≤0.25, 0.05≤z≤0.3; The phase structure of the high-stability positive electrode material is a P2 phase; The zinc ions doped in the sodium sites of the high-stability cathode material form O 2- -Zn 2+ -O 2- The prismatic structure; The transition metal sites in the high stability cathode material are doped with Cu 2+ Partially replace Mn 3+ .

2. The dual-site doped high-stability positive electrode material according to claim 1, characterized in that: The particle size Dv50 of the high-stability positive electrode material is between 1 μm and 50 μm.

3. A method for preparing a dual-site doped high-stability positive electrode material according to any one of claims 1 to 2, characterized in that: The preparation method comprises: Step S1, stirring and dissolving the required raw materials to obtain a mixed solution, specifically: weighing a soluble sodium source material, a zinc source material, a manganese source material, a copper source material and deionized water according to a stoichiometric ratio, adding them into a disperser, stirring and dissolving them uniformly, to obtain a mixed solution; Step S2, preparing the precursor gel by hydrothermal reaction, specifically: putting the mixed solution obtained above and the complexing agent into a hydrothermal reaction kettle, controlling the water bath temperature and adding ammonia water to adjust the pH value, stirring and reacting for a certain period of time to obtain the precursor gel; Step S3, drying and sintering the precursor gel to prepare a high-stability positive electrode material: drying the precursor gel obtained above in an oven, grinding it into powder, sintering it at high temperature, and cooling it to room temperature to obtain a dual-site doped high-stability positive electrode material.

4. The preparation method according to claim 3, characterized in that: The sodium source material includes: one or more of sodium hydroxide, sodium chloride, sodium fluoride, sodium nitrate, sodium carbonate, and sodium bicarbonate; The zinc source material includes: one or more of zinc chloride, zinc sulfate, zinc nitrate, zinc acetate, and zinc nitrate hexahydrate; The manganese source material includes: one or more of manganese nitrate, manganese sulfate, manganese acetate, manganese chloride, and acid manganese phosphate; The copper source material includes: one or more of copper chloride, copper sulfate, and copper nitrate.

5. The preparation method according to claim 3, characterized in that: The solid content of the mixed solution is between 10% and 50%; The mass of the complexing agent is 2%-15% of the mass of the mixed solution.

6. The preparation method according to claim 3, characterized in that: The pH value of the ammonia water is adjusted to be in the range of 5.5-6.

3.

7. The preparation method according to claim 3, characterized in that: The water bath temperature is between 30°C and 80°C; the stirring reaction time is 1 hour to 12 hours.

8. The preparation method according to claim 3, characterized in that: The drying temperature of the oven is 60° C.-120° C., and the drying time is 3 hours-15 hours.

9. The preparation method according to claim 3, characterized in that: The high temperature sintering is specifically carried out by heating the temperature to 750°C-1000°C at a heating rate of 1°C / min-10°C / min, and the heat preservation time is 8 hours-24 hours.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the dual-site doped high-stability positive electrode material as described in any one of claims 1-2.